2003
DOI: 10.1590/s1517-74912003000100010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ligature-induced periodontitis in pregnant Wistar rats

Abstract: The aim of this study was to evaluate the influence of ligature-induced periodontal disease in pregnant rats on their newborn's health parameters. Twenty-four female adult Wistar rats were divided into two groups: the control group (G1) and the group that was submitted to dental ligatures around second upper molars (G2). After the four week period of development of periodontitis, the female animals were mated with male adult Wistar rats. There were no differences in the body weight of females between the two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The results of this study are from a commonly used experimental rat model for periodontitis [4044]. The impetus for choosing the ligature model is that it promotes scenarios similar to food impaction between teeth in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are from a commonly used experimental rat model for periodontitis [4044]. The impetus for choosing the ligature model is that it promotes scenarios similar to food impaction between teeth in humans.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Animal models have also been used to study this association, however, without showing any clear tendency. 11 Despite the conflicting results, health practitioners need to be aware of the possibility of periodontal disease having an impact of negative outcomes on pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have shown no correlation between PLBW and maternal periodontal disease 7,8 . Published reports show that periodontitis during pregnancy increases bacteria and inflammatory mediators, which can enter the bloodstream and cause preterm membrane rupture and birth, increasing the potential for low birth weight 9 . Other experimental studies in rats show that ligature‐induced periodontitis promotes an increase in plasma levels of tumor necrosis factor‐α (TNF‐α) 10,11 .…”
mentioning
confidence: 99%
“…7,8 Published reports show that periodontitis during pregnancy increases bacteria and inflammatory mediators, which can enter the bloodstream and cause preterm membrane rupture and birth, increasing the potential for low birth weight. 9 Other experimental studies in rats show that ligature-induced periodontitis promotes an increase in plasma levels of tumor necrosis factor-a (TNF-a). 10,11 Sert et al 12 also reported increased levels of TNF-a and interleukin-6 (IL-6) in human mothers with periodontitis.…”
mentioning
confidence: 99%